Theory of Development of Personality: Need to Forgive - Beresnevičienė, Danguolė (Acta Paedagogica Vilnensia, 2005)
Articlc dcals with thc problcm of undcrstanding of process of forgiveness by philosophers, psychologists and psychotherapists. Among the first psychologists, analysing model of the process of forgiveness were Enright and Gassin. Japanese psychologists looking for the most effective ways of conflict solving described their model of the process of forgiveness as the conflict solving model (Ohbuchi and Takada). Many researchers are studying cross-cultural differences of process of forgiveness. In the theories of personality still nowadays exists different perspectives in psychology. There is no one theory of understanding of structure or process of development of personality. The first Lithuanian author to develop and original theory of personality was prof. L. Jovaiša, trying to integrate factors and trait theories, theory of activity, theory of motivation at etc. Trying to prolong his tradition, I described the structure and development of personality from humanistic as well as Jungian, psychoanalytical and neopsychoanalytical approaches. So the structure of personality consists of collective unconsciousness, individual unconsciousness, consciousness and collective consciousness. Hierarchy of needs are developing via life-span according pyramid, which is starting from the need to survive, second level contains sexual and economical needs, third level – need to have power and control, recognition, self-realization. These needs are describing as the need "to have". The other upper part of the pyramid consists of the need "to be", which is starting from the need to forgive to others and to yourself, later is developing the need for unconditional love to everybody and to everything, need to accept the life as it is, need to create and to develop intuition and in the top of the pyramid is the need to believe in God, oneself or the Absolute (this depends on the personal beliefs or religion of the personality). Needs of the personality are developing to the vertical and also to the horizontal directions. The process which fosters the development of the needs is the process of awareness. Growing personality is becoming more aware of his own needs, learning to forgive to the others and to himself help to reach the level of unconditional love to everybody and everything, to accept the life, to develop intuition and trust to the God.
Keywords: personality; development of personality; unconscousness; collective unconscousness; individual unconscousness; conscousness; collective conscousness; need to forgive to yourself and to others; hierrachy of needs; needs "to have" and needs "to be"